Effects of behaviour change communication: interventions for the prevention of bilharziasis in the districts of N’dali and Aguégués in Benin - Ahamidé, Josias Olutobi; Sossa, Charles Jérôme; Sissinto, Yolande; Yétongnon, Edmond; Ouendo, Edgard-Marius (Frontiers in Tropical Diseases, 2025)
BackgroundThe persistent endemicity of bilharziasis (schistosomiasis) in the districts of Aguégués (Agué) and N’dali underscores the need for targeted intervention. This study assessed the impact of a health education programme grounded in the behaviour change communication (BCC) framework aimed at improving awareness of health risks associated with poor hygiene practices.ObjectiveTo implement and evaluate an integrated communication model designed to promote behaviour change and reduce the incidence of urinary bilharzia in two endemic communities.MethodsA quasi-experimental study was conducted involving 106 households, divided equally into control (n=53) and experimental (n=53) groups, with school-aged children (8–14 years). The intervention, delivered from January to June 2023, applied an integrated communication model based on Ajzen’s theory of planned behaviour. Community health relays conducted biweekly awareness sessions over 6 months to educate households. Data were collected using KoboCollect and analysed through logistic regression and multivariate analysis in STATA. Urine samples were collected for laboratory analysis using Plouvier’s filtration sensitivity test. Descriptive statistics and confidence intervals were calculated using Student’s t-test in SPSS. Relative risk was assessed based on an estimation of incidence among the separate groups.ResultsOverall, the incidence within the exposed group was estimated as 11.32%, compared to 24.53% within the non-exposed group. Reinfection rates were significantly associated with sex across study groups. Compared to girls, boys had higher reinfection rates in both the exposed group (boys: 7.54%; girls: 3.77%) and non-exposed group (boys: 18.87%; girls: 5.66%). The qualitative variables “duration of communication sessions,” “frequency of communication sessions,” “topics of communication sessions,” “past behaviour of the household,” and “household intention for behaviour change” were statistically significant (p < 0.01) and had an effect on reducing the incidence of bilharzia in the experimental municipalities of Aguégués and N’Dali. Furthermore, the intention of the target population of N’dali and Aguégués to adopt the expected behaviour was studied using a prediction test, with an estimated relative risk of 0.46 and a confidence interval (CI) [0.48-0.52].ConclusionThe study proved effective in promoting health-related behaviour change and reducing bilharzia incidence. The model is recommended for broader implementation in bilharzia-endemic areas.